Contesting Patriotism: Culture, Power, and Strategy in the Peace Movement - Woehrle, Lynne M., (Rowman & Littlefield Publishers, 2008)
During war, space for debate shrinks. Narrow ideas of patriotism and democracy marginalize and silence opposition to militarism abroad and repression at home. Although powerful, these ideas encounter widespread resistance. Analyzing the official statements of 15 organizations from 1990-2005, the authors show that the U.S. peace movement strongly contested taken-for-granted assumptions regarding nationalism, religion, security, and global justice. Contesting Patriotism engages cutting-edge theories in social movements research to understand the ways that activists promote peace through their words. Concepts of culture, power, strategy, and identity are used to explain how movement organizations and activists contribute to social change. The diversity of organizations and conflicts studied make this book a unique and important contribution to peace building and to social movements scholarship.